A rapid method for detecting protein-nucleic acid interactions by protein induced fluorescence enhancement - Valuchova, Sona; Fulnecek, Jaroslav; Petrov, Alexander P; Tripsianes, Konstantinos; Riha, Karel (Scientific reports, 2016)
Many fundamental biological processes depend on intricate networks of interactions between proteins and nucleic acids and a quantitative description of these interactions is important for understanding cellular mechanisms governing DNA replication, transcription, or translation. Here we present a versatile method for rapid and quantitative assessment of protein/nucleic acid (NA) interactions. This method is based on protein induced fluorescence enhancement (PIFE), a phenomenon whereby protein binding increases the fluorescence of Cy3-like dyes. PIFE has mainly been used in single molecule studies to detect protein association with DNA or RNA. Here we applied PIFE for steady state quantification of protein/NA interactions by using microwell plate fluorescence readers (mwPIFE). We demonstrate the general applicability of mwPIFE for examining various aspects of protein/DNA interactions with examples from the restriction enzyme BamHI, and the DNA repair complexes Ku and XPF/ERCC1. These include determination of sequence and structure binding specificities, dissociation constants, detection of weak interactions, and the ability of a protein to translocate along DNA. mwPIFE represents an easy and high throughput method that does not require protein labeling and can be applied to a wide range of applications involving protein/NA interactions.
Keywords: Protein Binding; proteiny; Anisotropy; Fluorescent Dyes; fluorescenční spektrometrie; Deoxyribonuclease BamHI; fluorescenční mikroskopie; nukleové kyseliny; Transcription, Genetic; Protein Biosynthesis; proteosyntéza; deoxyribonukleasa BamHI; Fluorescence; antigen Ku; genetická transkripce; DNA Repair; oprava DNA; vazba proteinů; lidé; Microscopy, Fluorescence; RNA; Humans; anizotropie; Ku Autoantigen; fluorescenční barviva; replikace DNA; DNA; DNA Replication; Nucleic Acids; ionty; Spectrometry, Fluorescence; Ions; Proteins; fluorescence